Plasticity of Type I Interferon-Mediated Responses in Cancer Therapy: From Anti-tumor Immunity to Resistance - Budhwani, Megha; Mazzieri, Roberta; Dolcetti, Riccardo (Frontiers in Oncology, 2018)
The efficacy of several therapeutic strategies against cancer, including cytotoxic drugs, radiotherapy, targeted immunotherapies and oncolytic viruses, depend on intact type I interferon (IFN) signaling for the promotion of both direct (tumour cell inhibition) and indirect (anti-tumour immune responses) effects. Malfunctions of this pathway in tumour cells or in immune cells may be responsible for the lack of response or resistance. Although type I IFN signalling is required to trigger anti-tumour immunity, emerging evidence indicates that chronic activation of type I IFN pathway may be involved in mediating resistance to different cancer treatments. The plastic and dynamic features of type I IFN responses should be carefully considered to fully exploit the therapeutic potential of strategies targeting IFN signalling. Here, we review available evidence supporting the involvement of type I IFN signaling in mediating resistance to various cancer therapies and highlight the most promising modalities that are being tested to overcome resistance.